2018
DOI: 10.5194/amt-11-741-2018
|View full text |Cite
|
Sign up to set email alerts
|

Development of an instrument for direct ozone production rate measurements: measurement reliability and current limitations

Abstract: Abstract. Ground-level ozone (O 3 ) is an important pollutant that affects both global climate change and regional air quality, with the latter linked to detrimental effects on both human health and ecosystems. Ozone is not directly emitted in the atmosphere but is formed from chemical reactions involving volatile organic compounds (VOCs), nitrogen oxides (NO x = NO + NO 2 ) and sunlight. The photochemical nature of ozone makes the implementation of reduction strategies challenging and a good understanding of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…OH radicals are excited and detected using the A 2 + υ = 0 ← X 2 υ = 0 transition near 308 nm (Stevens et al, 1994). The net signal is measured by spectral modulation by tuning the wavelength on and off resonance in successive modulation cycles.…”
Section: Ho X Radical Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…OH radicals are excited and detected using the A 2 + υ = 0 ← X 2 υ = 0 transition near 308 nm (Stevens et al, 1994). The net signal is measured by spectral modulation by tuning the wavelength on and off resonance in successive modulation cycles.…”
Section: Ho X Radical Measurementsmentioning
confidence: 99%
“…For example, RO 2 radicals produced from the OH-initiated oxidation of small alkanes were found to produce a negligible yield of HO 2 (Stevens et al, 1994;Kanaya et al, 2001;Tan, et al, 2001;Creasey et al, 2002;Holland et al, 2003). However, recent laboratory studies have shown that there are interferences associated with measurements of HO 2 from the conversion of RO 2 radicals derived from the OH-initiated oxidation of alkenes and aromatics to HO 2 (and subsequently OH) through the reaction with NO.…”
Section: Contribution Of Ro 2 Interferences During Ho 2 Measurementsmentioning
confidence: 99%
“…As a result, the operational cost can be reduced and the number of monitoring stations can be scaled up. Finally, human involvement is typically required to operate some instruments, including "Ozone Analyzer" [57]. The O 3 proxy acts as a virtual sensor where the number of operators can be reduced.…”
Section: Case Studymentioning
confidence: 99%
“…The IRRONIC campaign site was located within a mixed deciduous forest (sugar maple, sycamore, tulip polar, ash and hickory trees) at the Indiana University Research and Teaching Preserve (IU-RTP) field lab (39.1908º N, 86.502º W) located approximately 2.5 km northeast of the center of the Indiana University campus, and 1 km from the IN 45/46 bypass at the northern perimeter. The goals of the campaign included an informal intercomparison of peroxy radical measurements by two different techniques (Kundu et al, 2019), an analysis of ozone production sensitivity at this site (Sklaveniti et al, 2018), a https://doi.org/10.5194/acp-2019-726 Preprint. Discussion started: 21 August 2019 c Author(s) 2019.…”
Section: Irronic Location and Supporting Measurementsmentioning
confidence: 99%
“…Measurements were conducted on top of two scaffolding platforms adjacent to the field lab, approximately 1.8 m from the ground. Additional information regarding the field site and the IRRONIC campaign can be found in Sklaveniti et al (2018) and Kundu et al (2019). Table 1 summarizes the major instrumentation employed during the campaign.…”
Section: Irronic Location and Supporting Measurementsmentioning
confidence: 99%